(untitled) (Research, Society and Development, 2022)
Starting in the 2000s, a series of mass demonstrations led to changes in governments in Eastern Europe, Central Asia, North Africa and Latin America. These large protests became known as the “color revolution”. According to the traditional press, such actions were carried out by different social segments that were unhappy with their governments, as well as protesting against dictatorships. However, there is evidence that “color revolutions” are geopolitical tools that make use of the democratic system to change governments. Therefore, the objective of this discussion is to reflect on aspects of the infrastructure that provide conditions for the “color revolutions” to be prepared and then executed, we will demonstrate how some actors move on the “surface” and in the “shadows” of the international network that operates the “color revolutions”. To achieve the objective, we carried out bibliographic research, as well as, we theoretically support the theory of Hybrid War.